Evaluating a paradigm shift from anterior decompression and fusion to muscle-preserving selective laminectomy: a single-center study of degenerative cervical myelopathy - Kitamura, Kazuya; de Dios, Eddie; Bodon, Gergely; Barany, Laszlo; MacDowall, Anna (Journal of Neurosurgery-Spine, 2022)
OBJECTIVE Muscle-preserving selective laminectomy (SL) is an alternative to conventional decompression surgery in patients with degenerative cervical myelopathy (DCM). It is less invasive, preserves the extensor musculature, and maintains the range of motion of the cervical spine. Therefore, the preferred treatment for DCM at the authors’ institution has changed from anterior decompression and fusion (ADF), including anterior cervical discectomy and fusion (ACDF) and anterior cervical corpectomy and fusion (ACCF), toward SL. The aim of this study was to evaluate surgical outcomes before and after this paradigm shift with patient-reported outcome measures (PROMs), complications, reoperations, and cost-effectiveness. METHODS This study was a retrospective register-based cohort study. All patients with DCM who underwent ADF or SL at the authors’ institution from 2008 to 2019 were reviewed. Using ANCOVA, changes in PROMs from baseline to the 2-year follow-up were compared between the two groups, adjusting for clinicodemographic parameters, baseline PROMs, number of decompressed levels, and MRI measurements (C2–7 Cobb angle, C2–7 sagittal vertical axis [SVA], and modified K-line interval [mK-line INT]). The PROMs, including the European Myelopathy Score (EMS), the Neck Disability Index (NDI), and the EQ-5D, were collected from the national Swedish Spine Register. Complications, reoperations, and in-hospital treatment costs were also compared between the two groups. RESULTS Ninety patients (mean age 60.7 years, 51 men [57%]) were included in the ADF group and 63 patients (mean age 68.8 years, 41 men [65%]) in the SL group. The ADF and SL groups had similar PROMs at baseline. The preoperative MR images showed similar C2–7 Cobb angles (10.7° [ADF] vs 14.1° [SL], p = 0.12) and mK-line INTs (4.08 vs 4.88 mm, p = 0.07), but different C2–7 SVA values (16.2 vs 19.3 mm, p = 0.04). The comparison of ANCOVA-adjusted mean changes in PROMs from baseline to the 2-year follow-up presented no significant differences between the groups (EMS, p = 0.901; NDI, p = 0.639; EQ-5D, p = 0.378; and EQ-5D health, p = 0.418). The overall complication rate was twice as high in the ADF group (22.2% vs 9.5%, p = 0.049), while the reoperation rate was comparable (16.7% vs 7.9%, p = 0.146). The average in-hospital treatment cost per patient was 6617 (USD) for SL, 7046 for ACDF, and 12,000 for ACCF. CONCLUSIONS SL provides similar PROMs after 2 years, a significantly lower complication rate, and better cost-effectiveness compared with ADF.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anterior decompression and fusion; cost-effectiveness; degenerative cervical myelopathy; muscle-preserving selective laminectomy; patient-reported outcome measure